Relationship between Giving Health Education to Mothers' Knowledge and Attitudes about Completeness of Immunization in Posyandu Bulo Village Walenrang District In 2018 - Lindriani Lindriani; Nilawati Uly (State Islamic University of Sunan Ampel, 2019)
One of the factors decline of immunization coverage is community understanding which is still limited. Even confused about immunization due to a lack of knowledge and attitudes of parents towards immunization. The purpose of this research is to know the relationship between giving health education to mother’s knowledge and attitudes about completeness of immunization in posyandu bulo village walenrang districtin 2018. The research design was used quasy-experiment with one group pre and post test design approach. The population in this research was all the mothers who came to bring her son to Posyandu for immunization. The sampling technique used total sampling with the total samples were 42 respondents. The data that has been collected then processed and analyzed by using computer and statistic program (SPSS) with T test-dependent. The results of this research showed the differences with the increasing of mothers’ knowledge after pre-test (p-value=0,01) and there were differences with the increasing of mothers’ knowledge after post-test (p-value=0,01). The conclusion in this research was there were Relationship Between Giving Health Education to Mother’s Knowledge and Attitudes About Completeness of Immunization in Posyandu Bulo Village Walenrang District in 2018. It is expected that the next researcher will perform direct observation on the completeness of immunizations.